2017
DOI: 10.1186/s12967-017-1130-y
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of miRNA-mRNA crosstalk in CD4+ T cells during HIV-1 infection by integrating transcriptome analyses

Abstract: BackgroundHIV-1-infected long-term nonprogressors (LTNPs) are characterized by infection with HIV-1 more than 7–10 years, but keeping high CD4+ T cell counts and low viral load in the absence of antiretroviral treatment, while loss of CD4+ T cells and high viral load were observed in the most of HIV-1-infected individuals with chronic progressors (CPs) However, the mechanisms of different clinical outcomes in HIV-1 infection needs to be further resolved.MethodsTo identify microRNAs (miRNAs) and their target ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 68 publications
2
11
0
Order By: Relevance
“…Furthermore, the majority of women who participated in the study were carrying HIV-1 for greater than 5 years (Table 1), thus it is suggested these two miRNAs could be used to monitor AIDS progression in HIV-1 infected women. Indeed, our finding is in agreement with a previous study in which miR-630 was reported as a biomarker in chronic progressors of HIV-1 63 . Interestingly, our HM exosomal miRNA data from the South Africa cohort where HIV-1 infected women were carrying HIV-1 load < 1 year (data not shown) showed downregulation of these miRNAs identified in the current study and correlated with a recent report where it was shown that acute HIV-1 leads www.nature.com/scientificreports/ to downregulation of miRNAs 57 .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Furthermore, the majority of women who participated in the study were carrying HIV-1 for greater than 5 years (Table 1), thus it is suggested these two miRNAs could be used to monitor AIDS progression in HIV-1 infected women. Indeed, our finding is in agreement with a previous study in which miR-630 was reported as a biomarker in chronic progressors of HIV-1 63 . Interestingly, our HM exosomal miRNA data from the South Africa cohort where HIV-1 infected women were carrying HIV-1 load < 1 year (data not shown) showed downregulation of these miRNAs identified in the current study and correlated with a recent report where it was shown that acute HIV-1 leads www.nature.com/scientificreports/ to downregulation of miRNAs 57 .…”
Section: Discussionsupporting
confidence: 94%
“…miRNAs are thought to be involved in mediating immune suppression, establishment of viral latency 59,64 or suppressing HIV-1 replication via decreasing HIV-1 dependency factors 65 . Some of the miRNAs we have identified have previously been implicated in HIV-1 infection including miR-630, miR-4516, miR-16-5p, miR-378, miR-93, miR-23, miR-30a 57,63,[66][67][68][69] thus strongly suggesting the reliability of the NanoString data obtained in the current study. Further, it has been described that NanoString can perform miRNA profiling with digital precision and the results do not require further validation by another method 70 .…”
Section: Discussionsupporting
confidence: 70%
“…To understand the role of differentially expressed circRNAs, Gene Ontology (GO) analysis and KEGG (Kyoto Encyclopedia of Genes and Genomes) were performed to construct meaningful annotation of genes as a whole network [23]. At the same time, we also constructed a circRNA-miRNA-mRNA network in transcripts.…”
Section: Functional Network Analysis For the Differential Circrnas Anmentioning
confidence: 99%
“…These data showed a significant fold-change value in the gene expression of at least one gene. Figure 1B lists the common genes of the two databases from the GEO [ 21 ], combined with our microarray results. These 174 common genes are shown by the Venn diagrams, using the false discovery rate (0.05), p -values less than 0.05, and two-fold changes, which may be potentially involved in PCa progression from all three microarrays.…”
Section: Resultsmentioning
confidence: 99%
“…The GO category was classified by Fisher's exact test, and the p-value was corrected by the false discovery rate (FDR) calculation include molecular function (MF), and biological process (BP). Criteria used for the GO and IPA analyses have been described previously [ 21 , 36 , 37 ].…”
Section: Methodsmentioning
confidence: 99%